Thyroidectomy in elderly ; is it safe? - Alnaser , Mumtaz Khudhur Hanna; Kamal, Zuhair Basheer; Wardia, Wissam Isam; Basheer , Bashar Hazim (AL-Kindy College Medical Journal, 2022)
Background: The prevalence of thyroid nodules rise with age and different data available about the risks of thyroid surgery in old age people. In general, old age could be a predictor of perioperative mortality and morbidity. The aim of this study is to prove if there is increased risk accompanying thyroidectomy in elderly patients. Subjects and Methods: Prospective study of one surgeon of study sample undergoing thyroid surgery at Al-Kindy teaching hospital and Saint Raphael hospital .This study was including two groups; group (A) involved patients 65 years and older, group (B) involved patients below 65 years old who were subjected to thyroidectomy. Taking in consideration histopathology results, indications of surgery (compressive symptoms, suspicious or confirmed malignancy, toxic goiter and recurrent goiter) and complications (including rates of temporary and permanent hypocalcaemia, temporary and permanent RLN paralysis, postoperative hematoma, wound infection and seroma), in addition to the risk of perioperative mortality. Results: There were 574 patients below 65 years and 127 elderly patients (>=65 years) who underwent thyroidectomy between January 2015 and December of 2018. There were no deaths in either group; no one had bilateral RLN paralysis. Old age patients had a lower frequency of complications in comparison to the younger counterparts, including transient hypocalcaemia (3.1% vs 14.8%, respectively) and temporary RLN injury (0% vs 0.69%, respectively), in addition to permanent RLN injury (0% vs 0.34%, respectively). Conclusions: Thyroidectomy in elderly is safe as compared to younger patients regarding perioperative complications